Development of Hand Movement Assistive Devices for Mild Stroke Patients Based on Arduino Uno - Dian Saadah; Siswiyanti Siswiyanti; Eko Budiraharjo; Eko Budihartono (Yayasan Banu Haji Samsudin, 2025)
Stroke is one of the leading causes of physical disability worldwide, including in Indonesia. In the Tegal area, the number of stroke sufferers continues to increase, causing many individuals to experience difficulties in performing daily activities, especially impaired motor function in the hands. Rehabilitation is an important step in the recovery of stroke patients, but the facilities and rehabilitation aids available in the Tegal area are still limited and expensive. This study aims to design and develop an Arduino Uno-based hand motion aid that is affordable and easily accessible to stroke patients in the Tegal area. The research method includes anthropometric methods with the results taken as the largest percentile, namely P95 in cm Lij (2.4), Pij (6.6), Ljt (2.1), Pjt (8), Ljtg (2.1), Pjtg (8.7), Pjm (2.1), Ljm (8.2), Pjk (1.9), Ljk (6.2), Pt (19.5), Ptt (10.9), Ltmk (9.1), Ltij (11.8), Ttij (6.5), Ttm (3.3), Tij (1.9), Tj (1.6), Ltm (10.9), Ptm (13.8), Jjk (20.6), Dgmak (6.6), Dgmin (4.5), Tgkt (6.7), Lkt (11.1). Testing on ten mild hand stroke patients aged 30-70 years, as well as evaluation of effectiveness through the distribution of questionnaires. The results of the study showed that the developed assistive device significantly improved the patient's hand motor function, with 40% of respondents agreeing that the device is easy to install and remove, and 30% agreeing that it can be used independently. The device also received positive responses regarding its comfort and effectiveness, with 50% of respondents agreeing that the device responded well to hand stimulation. In conclusion, the Arduino Uno-based hand motor aid has great potential for use in the rehabilitation of stroke patients in Tegal, and can be an effective solution to improve their quality of life.